Information Security and Privacy 18th Australasian Conference, ACISP 2013, Brisbane, Australia, July 1-3, 2013. Proceedings - Boyd, Colin; Simpson, Leonie; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed conference proceedings of the 18th Australasian Conference on Information Security and Privacy, ACISP 2013, held in Brisbane, Australia, in July 2013. The 28 revised full papers presented were carefully selected from 78 submissions. Conference papers are organized in technical sessions, covering topics of Cryptoanalysis, RSA, Lattices and Security Proofs, Public Key Cryptography, Hashing, Signatures, Passwords, Mobile Security, and Secret Sharing.
Analysing the IOBC authenticated encryption mode -- A Chosen IV Related Key Attack on Grain -- Cryptanalysis of Helix and Phelix Revisited -- Toward Separating the Strong Adaptive Pseudo-Freeness from the Strong RSA Assumption -- Minkowski sum based lattice construction for multivariate simultaneous -- Coppersmith's technique and applications to RSA -- Lattices and security proofs -- Adaptive Precision Floating Point LL -- Better Lattice Constructions for Solving Multivariate Linear Equations Modulo Unknown Divisors -- Key-Dependent Message Chosen-Ciphertext Security of the Cramer-Shoup Cryptosystem -- Black-Box Separations and their Adaptability to the Non-Uniform Model -- Injective Encodings to Elliptic Curves -- Membership Encryption and Its Applications -- Towards Privacy Preserving Mobile Internet Communications -- Count-min sketches for estimating password frequency with Hamming Distance -- Secret sharing -- A rational secret sharing protocol with unconditional security in the synchronous setting -- Secret Sharing Schemes with Conversion Protocol to Achieve Short Share-Size and Extendibility to Multiparty Computation.
Keywords: Computer science; Computer security; Data encryption (Computer science).; Coding theory; Application software; Management information systems; E-commerce.; Computer Science; Systems and Data Security; Data Encryption; Management of Computing and Information Systems; Coding and Information Theory; Computer Appl. in Administrative Data Processing; e-Commerce/e-business.; Electronic books